A report of an experience of occupational therapy in a group with individuals with rheumatic diseases - Noordhoek, Johanna; Silva, Maria Cristina de Oliveira; Torquetti, Aline; Cisneros, Ligia de Loiola (Revista de Terapia Ocupacional da Universidade de São Paulo, 2009)
The individual with a rheumatic disease presents physiological and anatomical changes which interfere with performance of the daily activities. Occupational therapy working with health promotion for this population aims to improve functional, social and emotional aspects to help achieve better performance of their daily activities and to promote better quality of life. The aim of this paper is to relate a group of orientation for patients with rheumatic diseases. The proportions are based on empiric experience of the group: "Orientation for individuals with rheumatic diseases" The group is a community based project of The Federal University of Minas Gerais.This educational process offered through therapeutic workshops based on ludic-recreative activities. The strategy enables education, socialization and progress of skills to face the disease and the performance of their daily role in life.